Bilateral Temporomandibular Joint ankylosis related to trauma - Víctor Manuel González Olmedo; Rodrigo Liceaga Reyes; David Garcidueñas Briceño (Universidad Nacional de Colombia, 2013)
Temporomandibular joint ankylosis may be defined as the partial or total fusion of the articular surfaces with bony or fibrous tissue. It has been related with trauma events to the condylar process, which may derive in lack of development of the mandible, causing facial asymmetries and compromising normal function. Numerous techniques have been described for treatment, within which include the aggressive excision of the ankylotic mass, with or without the employment of interposition material and the use of autologous graft for reconstruction. The choice of treatment becomes a challenge to the surgeon, because of the high incidence of recurrence. We present a case of a male patient with history of trauma, under the diagnosis of bilateral temporomandibular joint ankylosis; which was treated through arthroplasty, placement of interposition material and autologous graft of coronoid process.